The Effect of Change Leadership on Adaptive Performance: Meaningful Work as A Mediating Variable (International Journal of Scientific Research and Management (IJSRM), 2024)
Organizational change is one continuous study to be carried out because organizational change will definitely occur. The role of the leader as the spearhead of the organization needs to be studied because it will impact on the subordinate’s perception and behavior, one of which is so that they have adaptive performance. Of course, to achieve adaptive performance there needs to be a positive perception of own work. The aims of this research is to examine the effect of change leadership on adaptive performance: testing the mediating role of meaningful work on the influence of change leadership on adaptive performance. This research uses a quantitative approach, with a purposive sampling technique. The data used is primary data through surveys distributed online by a sample size was 350 respondents. The data analysis technique uses the Structural Equation Modeling (SEM) test. The research results proven that change leadership has a significant positive effect on adaptive performance. Furthermore, meaningful work mediates the influence of change leadership on adaptive performance.